CANADA: A MULTICULTURAL AND ECONOMICALLY DEVELOPED NATION (Ustozlar uchun, 2026)
Canada is widely recognized as one of the most developed and multicultural countries in the world. This study analyzes the relationship between multiculturalism and economic development in Canada. Using qualitative and secondary data analysis, the research explores how diversity contributes to economic growth and social stability. The findings suggest that Canada’s inclusive policies and strong institutional framework play a key role in its success.